2022
DOI: 10.3390/jcm11092526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Matrix Size Reduction on Textural Information in Clinical Magnetic Resonance Imaging

Abstract: The selection of the matrix size is an important element of the magnetic resonance imaging (MRI) process, and has a significant impact on the acquired image quality. Signal to noise ratio, often used to assess MR image quality, has its limitations. Thus, for this purpose we propose a novel approach: the use of texture analysis as an index of the image quality that is sensitive for the change of matrix size. Image texture in biomedical images represents tissue and organ structures visualized via medical imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Such parameters, if properly selected and repeatable, are very useful for reliable characterization of internal human organs independently of the image modality used. It has been demonstrated that texture analysis can be usefully implemented for classifying median nerves in carpal tunnel syndrome in echo images [3], diagnosis of cysts and granulomas in intra-oral radiographs [4] or quality assessment of MR images [5]. There is also free software available for texture feature evaluation, such as MaZda [6] and its successor qMaZda [7], widely used by many researchers to facilitate texture analysis in many medical image processing tasks.…”
Section: Texture Analysis In Musculoskeletal Imagingmentioning
confidence: 99%
“…Such parameters, if properly selected and repeatable, are very useful for reliable characterization of internal human organs independently of the image modality used. It has been demonstrated that texture analysis can be usefully implemented for classifying median nerves in carpal tunnel syndrome in echo images [3], diagnosis of cysts and granulomas in intra-oral radiographs [4] or quality assessment of MR images [5]. There is also free software available for texture feature evaluation, such as MaZda [6] and its successor qMaZda [7], widely used by many researchers to facilitate texture analysis in many medical image processing tasks.…”
Section: Texture Analysis In Musculoskeletal Imagingmentioning
confidence: 99%